2015
DOI: 10.1016/j.pep.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of a correctly folded mouse α-defensin, cryptdin-4, by refolding during inclusion body solubilization

Abstract: Mammalian α-defensins contribute to innate immunity by exerting antimicrobial activity against various pathogens. To perform structural and functional analysis of α-defensins, large amounts of α-defensins are essential. Although many expression systems for the production of recombinant α-defensins have been developed, attempts to obtain large amounts of α-defensins have been only moderately successful. Therefore, in this study, we applied a previously developed aggregation-prone protein coexpression method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In some studies, the coexpression of an insoluble partner protein has been reported to enhance the inclusion body formation of the target peptide. Tomisawa et al succeeded in expressing a large amount of cysteine‐rich AMPs such as antibacterial factor‐2 and the mouse α‐defensin, cryptidin‐4 in E. coli cells as inclusion body by coexpression of aggregation‐prone partner protein . Saito et al reported the enhanced expression of somatomedin C by coexpression of insulin‐like growth factor I .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, the coexpression of an insoluble partner protein has been reported to enhance the inclusion body formation of the target peptide. Tomisawa et al succeeded in expressing a large amount of cysteine‐rich AMPs such as antibacterial factor‐2 and the mouse α‐defensin, cryptidin‐4 in E. coli cells as inclusion body by coexpression of aggregation‐prone partner protein . Saito et al reported the enhanced expression of somatomedin C by coexpression of insulin‐like growth factor I .…”
Section: Discussionmentioning
confidence: 99%
“…Recently we developed a coexpression method that enhanced the inclusion body formation of the target peptide by coexpression of an aggregation‐prone protein as a partner protein. The charge of the partner protein was previously shown to affect the inclusion body formation by the target peptide, with an oppositely charged partner protein being considered most suitable for efficient formation of inclusion bodies of the target peptide .…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used host cell has been Escherichia coli mainly because it grows easily, fast and is inexpensive, and also because it is a well-established expression system (Pazgier and Lubkowski 2006; Tomisawa et al. 2015). Disadvantages of the use of these recombinant strategies to produce HDPs are their potential toxicity to the host and their susceptibility to proteolytic degradation (Li 2009).…”
Section: Production Of Hdps For Biological and Clinical Applicationsmentioning
confidence: 99%
“…The formation of inclusion bodies as a novel way to prevent degradation and improve productivity has also been assayed with promising results compared to the conventional method (Tomisawa et al. 2015). …”
Section: Production Of Hdps For Biological and Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation